2017
DOI: 10.1038/ncomms15754
|View full text |Cite
|
Sign up to set email alerts
|

Constriction of the mitochondrial inner compartment is a priming event for mitochondrial division

Abstract: Mitochondrial division is critical for the maintenance and regulation of mitochondrial function, quality and distribution. This process is controlled by cytosolic actin-based constriction machinery and dynamin-related protein 1 (Drp1) on mitochondrial outer membrane (OMM). Although mitochondrial physiology, including oxidative phosphorylation, is also important for efficient mitochondrial division, morphological alterations of the mitochondrial inner-membrane (IMM) have not been clearly elucidated. Here we rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
128
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(141 citation statements)
references
References 72 publications
(118 reference statements)
13
128
0
Order By: Relevance
“…As further evidence for excess membrane tension, we observed pearling modes on 11% of dividing mitochondria (N=88) (SFig. 9e), also previously reported in neuronal mitochondria [39,40]. We found that mitochondria exhibiting pearling modes eventually underwent fission of at least one of the constriction sites (100%, N=10).…”
Section: Fission Events Are Characterized By Increased Membrane Tensionsupporting
confidence: 84%
See 1 more Smart Citation
“…As further evidence for excess membrane tension, we observed pearling modes on 11% of dividing mitochondria (N=88) (SFig. 9e), also previously reported in neuronal mitochondria [39,40]. We found that mitochondria exhibiting pearling modes eventually underwent fission of at least one of the constriction sites (100%, N=10).…”
Section: Fission Events Are Characterized By Increased Membrane Tensionsupporting
confidence: 84%
“…Furthermore, increases in Ca2+ leading up to mitochondrial division [12,40,54] SIM images were reconstructed using a custom 2D linear SIM reconstruction software obtained at Janelia farm, as previously described [58,59]. Images were reconstructed using a generalized Weiner filter parameter value of 0.02-0.05 with background levels of ~100.…”
Section: Mitochondrial Fission Differs From Other Fission Processes Smentioning
confidence: 99%
“…In light of the monophyletic origin of mitochondria, we and others postulated that metazoan mitochondria would also harbour a fission machinery located in the matrix 8,22 . Indeed, fission of the matrix compartment has been observed in the absence of outer membrane fission in several metazoans 2326 . However, previous attempts at bioinformatic identification of a bacteria-derived division machinery in metazoan mitochondria based on sequence similarity have failed 10,27 .…”
Section: Introductionmentioning
confidence: 99%
“…with cholesterol in the IMM (Gerhold et al, 2015) . Additionally, mammalian cell culture 522 models show that constriction of the IMM is an important early step in mitochondrial fission 523 (Cho et al, 2017), and preferentially occurs where the replicating mtDNA nucleoid is located 524 (Lewis, Uchiyama and Nunnari, 2016). The morphological and physiological defects we 525 observed upon loss of twnk-1 may imply that, in C. elegans, Twinkle serves as an IMM protein 526…”
mentioning
confidence: 99%